Green city as approach to Conservatism the Resources and Protection the Environment from the Pollution Locality [911-913-915] Study - the Study Area Al-karrada alsharqiya - mohammed, Nada khaleefah; Aljanabi, Najwa Sadiq (Iraqi Journal of Architecture and Planning, 2018)
The evolution of new concepts for sustainable planning and development of cities in the world and use these concepts and their practical application and success significantly especially in the developed countries and applied in some developing countries leads us to search for new mechanisms that could be used in Iraq and pave the way for sustainable development of the urban environment of cities. The urban environment of the city of Karrada need rise include social, economic, urban, environmental, and this only by using new methods of management and planning are different from those that dealt with the city, focusing on the urban side only. And based on the nature and aesthetic achievement of the principles and objectives of the city of Wuxi, which represent the privacy of Baghdad and Iraq at large is not a simple process, but need to share all of the State, individuals and non-governmental organizations and the private sector.